PENAMPILAN RANDOM AMPLIFIED POLYMORPHIC DNA PADA Azadirachta indica A. Juss DARI TAMAN NASIONAL BALURAN - Fajarudin Ahmad; Yuyu S. Poerba (Jurnal Teknologi Lingkungan, 2010)
Azadirachta indica A. Juss (Apocynaceae) is a large tree of the lowland tropical rain forest of Southeast Asia that occurs in Thailand, the Malay Peninsula, on the island of Java (East Java) and Lesser Sunda Islands. Its economic value was in its wood (timber), and as medicinal plant. The information on genetic diversity of the species is very limited. Hence studies were initiated and genetic diversity estimated using RAPD markers in 27 accessions of A.indica procured from three geographical regions of TN Baluran and Balai Litbang Kehutanan. Seven selected Operon primers (10 mer) generated a total of 133 consistent amplification products ranging from 132 bp to 5.6 Kb. The cluster analysis separated the 27 individuals into 2 clusters. The range of genetic dissimilarityvalue among samples was from 0.07 to 0.33, while genetic distance among populations was from 0.04 to 0.10. These values showed that A. indica from TN Baluran was not genetically diverse population. Key words: Azadirachta indica, genetic diversity, RAPD